Microbic spectrum of the vagina and myomatous knot at sick of the hysteromyoma - A Н Rymashevsky; E S Nikitin; E G Svirava; A E Samsonov; J L Naboka (RUDN Journal of Medicine, 2012)
22 patients of genital age with a hysteromyoma, not receiving antibacterial and a hormonetherapy in the preoperative period are surveyed. To the given group of patients operation with organ conservation is executed. To all patients bacteriological research of a vaginal microflora and a biological material taken of myomatous knots is conducted. At all women with a hysteromyoma were observed dysbiotic disturbances of a microflora of a vagina, in the form of concentration depression of lacto- bacterius and bifidobacteria and сoncentration augmentation of peptokokkus. At 9% of patients in myomatous knot growth of microorganisms is not taped. In 91% of cases myomatous knots are inseminated not clostridial anaerobic bacteria. Among the microorganisms allocated in myomatous knot the most part have made peptostreptokokkus. The conclusion. By results of the received data it is possible to assume that hysteromyoma presence is bound to dissemination not clostridial anaerobic bacteria.